Doctor or Monster? The Pink Tide and Its Aftermath. (March 2022) - Barbosa dos Santos, Fabio Luis; Feldmann, Daniel
The recent evolution of capitalism has shifted the ground on which developmentalism stood as a civilizing utopia in Latin America, making the neodevelopmentalism that inspired different nuances of progressivism in the twenty-first century an idea "out of place." Starting from this premise, the notions of progressivism as regression and containment as accelerating desocialization form the foundations of an interpretation of the Pink Tide that emphasizes the contradictions inherent in its own dynamics, which reinforced the neoliberal rationale. The attempt to govern social tensions through containment of the ongoing dissociative movement did not stop the regression of the structure of production and the intensification of a self-destructive social dynamic. Progressivism is revealed as a political rationale that is different from but not contradictory to its opponents in a reality in which capital governs as a totalizing extraparliamentary force. A evolução recente do capitalismo modificou as bases materiais que davam sentido ao desenvolvimentismo como utopia civilizatória na América Latina, tornando o neodesenvolvimentismo que inspirou diferentes nuances de progressismo no século XXI, uma ideia fora do lugar. A partir desta premissa, são discutidas as noções de progressismo como regressão e de contenção como aceleracion de dissocializacion, como alicerces de uma interpretação da onda progressista que enfatiza as contradições inerentes à sua própria dinâmica que reforçou a razão neoliberal. A pretensão de governar as tensões sociais por meio de políticas de contenção do movimento dissocializante em curso não evitou a regressão da estrutura produtiva e o aprofundamento de uma dinâmica social autofágica. O progressismo revela-se como uma racionalidade política diferente, mas não contraditória em relação aos seus opositores em uma realidade em que o capital se impõe como uma força extra-parlamentar totalizante.